Langerhans Cell Histiocytosis of the Adult Cervical Spine: A Case Report and Literature Review - Schär, Ralph T.; Hewer, Ekkehard; Ulrich, Christian T. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
A 36-year-old man was diagnosed with Langerhans cell histiocytosis (LCH) of the cervical spine with a unifocal expansive osteolytic lesion of C4. The surgical management with a 2-year follow-up and a review of the literature on LCH of the cervical spine are presented. Although a rare condition, LCH is an important differential diagnosis of any osteolytic lesion in the cervical spine with localized pain in a young adult patient. Review of the literature suggests a higher prevalence of LCH lesions affecting the cervical spine as compared with the thoracic or lumbar spine than historically reported.
Keywords: Langerhans cell histiocytosis; eosinophilic granuloma; cervical spine; spinal neoplasms